Fractionation of organic liquid mixtures by reverse osmosis. - Fang, Yi. (University of Ottawa (Canada), 1990)
A systematic investigation has been conducted to demonstrate the general applicability of reverse osmosis (RO) fractionation of organic liquid mixtures by laboratory prepared cellulose acetate butyrate (CAB) and aromatic polyamide (PA) membranes. Surface excess values have been determined by liquid chromatography (LC) technique for the four model organic liquid mixtures for CAB and PA materials. The principal findings of this study are: (i) separations take place in all the four model organic liquid mixtures, and PA membranes given separations higher than CAB membranes under same experimental conditions; (ii) preferential sorption exists in all the four model systems for CAB and PA materials, (iii) the RO results are explained by the combined consideration of surface excess data determined from LC, and Stokes' Law radius calculated from literature data.
Keywords: Engineering, Chemical.